The Development of Dorsal Nasal Cyst Formation after Rhinoplasty and Its Reconstruction with Conchal Cartilage - Tolgar Lütfi Kumral; Yavuz Uyar; Güven Yıldırım; Güler Berkiten; Yavuz Atar; Enes Ataç (Case Reports in Otolaryngology)
The dorsal nasal cyst formation is a rare and late complication of rhinoplasty. It has been rarely reported in the literature and it is usually mucous cysts. Migration and planting to the subcutaneous space during the surgical procedure has been recognized as the formation mechanism. This case report has presented 42-year-old male patient with a destructing dorsal nasal mucous cyst that developed 10 years after the rhinoplasty operation. There was no complication in the primary rhinoplasty and the patient was satisfied with his appearance. There was a swelling of the nasal dorsum over the past year and surgical excision of the cyst was performed. During the surgery, the defect was reconstructed with conchal cartilage. There was no recurrence during follow-up.